Arctic Ocean Boundary Exchanges: A Review - Bacon, Sheldon; Naveira Garabato, Alberto; Aksenov, Yevgeny; Brown, N.J.; Tsubouchi, Takamasa (Oceanography, 2022)
The Arctic Ocean has long been—and to a large extent remains—a data-sparse region. Paucity of ocean and atmosphere measurements impacts the fidelity of atmospheric reanalyses, and ungauged rivers lead to uncertainties in measurement-based estimates of river runoff. However, there exists a data resource that can provide material help: sustained (long-term) ice and ocean measurements around the Arctic Ocean boundary. The Arctic Ocean is surrounded by land and connects to adjacent ocean basins via four main gateways: to the Pacific through Bering Strait, to the Atlantic through Davis Strait, and to the Nordic Seas via Fram Strait and the Barents Sea Opening. In addition, the Nordic Seas connect to the Atlantic across the Greenland-Iceland-Scotland Ridge, which has a substantial measurement history. Inverse methods combine these data sets to generate conservative velocity fields that are then used to generate estimates of surface fluxes of heat and freshwater as well as other quantities of interest, including net biogeochemical fluxes and (with other methods) estimates of ocean water transformation rates. Data resources are available to greatly extend the duration and the temporal resolution of present analyses.